Rainbow table to crack password using MD5 hashing algorithm - Kumar, Himanshu; Kumar, Sudhanshu; Joseph, Remya; Kumar, Dhananjay; Shrinarayan Singh, Sunil Kumar; Kumar, Ajay; Kumar, Praveen (2013 IEEE Conference on Information and Communication Technologies, 2013)
Rainbow tables are basically huge tables filled with hash values and are used to find required password. Rainbow Table is used by the hackers to find the password by reversing the hashing function. Hashing the plaintext or password is a 1-way function which implies that hash can't be decrypted to find the required password[10]. To authenticate the user a system takes the hash value generated by the hash function on user's computer and it is compared with the hash value stored in the table on the server machine. If the hash matches, then the user is authenticated and can access the system. Rainbow tables are used to crack the password in short amount of time as compared to brute force technique, but it takes a lot of storage to hold rainbow table itself[1]. It is the most efficient methods for cracking passwords. This paper presents the implementation of Rainbow tables for cracking passwords of operating systems such as Windows7 and application which uses Message Digest v5(MD5) and Simple Hash Algorithmv1(SHA1) as their password hashing mechanism. It discusses the functionality of Rainbow Tables and its advantages over conventional brute-force approach and the usage of rainbow table to crack windows password.